2003
DOI: 10.1021/tx034005w
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Perfluorooctanoic Acid to Rat and Human Plasma Proteins

Abstract: Perfluorooctanoic acid (PFOA) is a commercially important organic fluorochemical and is considered to have a long half-life in human blood. In this paper, PFOA binding to rat and human plasma proteins was investigated. On the basis of results from size-exclusion chromatography and ligand blotting, most PFOA was in protein-bound form in male and female rat plasma, and the primary PFOA binding protein in plasma was serum albumin. PFOA binding to rat serum albumin (RSA) in the gas phase was observed by electrospr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
273
2
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 345 publications
(297 citation statements)
references
References 50 publications
18
273
2
4
Order By: Relevance
“…PFCs are distributed mainly to the liver and blood where they bind to serum proteins, mainly albumin (Han et al 2003;Jones et al 2003), and they are poorly eliminated in humans and have serum half-lives between 2 and 9 years (Lau et al 2007;Olsen et al 2007;Bartell et al 2010;Brede et al 2010;Seals et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…PFCs are distributed mainly to the liver and blood where they bind to serum proteins, mainly albumin (Han et al 2003;Jones et al 2003), and they are poorly eliminated in humans and have serum half-lives between 2 and 9 years (Lau et al 2007;Olsen et al 2007;Bartell et al 2010;Brede et al 2010;Seals et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Based on these results as well as environmental and human exposure concentrations of PFOS, it was concluded that the chemical would not displace hormones from serum proteins. In another report by Han et al (2003), binding of PFOA to rat and human plasma proteins were investigated. From sizeexclusion and ligand-blotting experiments, it was found that PFOA bound primarily to serum albumin in plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Worker EKG results and C-reactive protein measurements were also not associated with PFOA. Although Kaplan offered no additional hypotheses or suggested causal models (Hernán et al 2002), PFOA has been shown to bind or be carried on blood albumin (Han et al 2003) and beta-lipoproteins (KerstnerWood et al 2003) in the rat, monkey and human; thus, a positive non-causal correlation remains a possibility.…”
Section: Introductionmentioning
confidence: 99%